Geotechnics of roads : fundamentals - Caicedo, Bernardo (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
"This work discusses mechanistic approaches to the geotechnics of roads, which are based on the mechanical behavior of materials and on the physical relationships of continuum mechanics. The application of such approaches could allow the development of new technical solutions towards increased sustainability in the use of natural resources. However, their success requires a deep understanding of the behavior of the constituent materials, made possible by recent advances in geotechnical engineering. This book focuses on flexible pavements or unpaved roads, since the behavior of unbound granular materials and soil support is crucial in the performance of those structures."--Provided by publisher.
"A Balkema book."
Includes bibliographical references and index.
H.B
Description based on print version record and CIP data provided by publisher.
Keywords: Geotechnical engineering; Roads -- Design and construction; Road materials; Soil mechanics